Pengaruh Rebusan Lidah Buaya Terhadap Penurunan Kadar Gula Darah Pada Pasien Diabetes Melitus Tipe II di Desa Lampaseh Lhok - Putri Eliza; Urip Pratama; Nurul Sakdah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Type 2 diabetes mellitus has now become a widespread health issue with serious implications for public health. In an effort to support non-pharmacological management, the use of aloe vera (Aloe vera) decoction is one option being considered, given that this plant contains bioactive components such as aloin, emodin, and polysaccharides that have the potential to help lower blood glucose levels. This study aims to examine the effect of consuming aloe vera (Aloe vera) decoction on lowering blood sugar levels in patients with type 2 diabetes mellitus in Lampaseh Lhok Village, Montasik Subdistrict, Aceh Besar. The research was conducted from June 19 to 28, 2025, in that area. The study design employed a quantitative research approach using a quasi-experimental design with a one-group pretest-posttest model. The study population consisted of 38 patients with type 2 diabetes mellitus, while the sample comprised 15 respondents. Sampling was conducted using purposive sampling. The measurement tools included a glucometer and an observation sheet. Based on the data analysis results, a decrease in blood glucose levels was observed after the respondents consumed the aloe vera decoction. The Wilcoxon signed-rank test yielded a p-value of 0.001 (< 0.05), leading to the conclusion that the administration of the aloe vera (Aloe vera) decoction has a significant effect on reducing blood glucose levels in the respondents. Therefore, respondents are advised to drink aloe vera tea at least once a day as an alternative measure to help control blood glucose levels.